1993
DOI: 10.1161/01.cir.88.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Platelet membrane activation markers are predictive for increased risk of acute ischemic events after PTCA.

Abstract: BACKGROUND We wished to investigate whether platelet activation is related to the clinical outcome during the 24 hours immediately after elective percutaneous transluminal coronary angioplasty (PTCA). METHODS AND RESULTS In 102 patients with high-grade coronary stenosis admitted for elective PTCA, preprocedural platelet activation was characterized by flow cytometric measurement of the proteins CD62, CD63, and thrombospondin expressed on the platelet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(129 citation statements)
references
References 30 publications
9
118
0
2
Order By: Relevance
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 86%
“…11 ) The predictors of acute complications such as female gender, 12) advanced age, 13) lesion characteristics, 14) and haemostatic variables 15) have a poor practical value. 1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that coronary angioplasty induces platelet activation (Dehmer et al, 1997), and increased platelet activity is associated not only with ischemiareperfusion injury at the immediate stage, but also with restenosis at the late stage after coronary angioplasty (Tschoepe et al, 1993;Murasaki et al, 2007;Osmancik et al, 2008). In this study, we also found that the plasma P-selectin level at 5 min after PCI was positively correlated to inflation pressure, indicating that the increase in circulating P-selectin levels is partly due to vascular injury caused by coronary angioplasty.…”
Section: Fig 4 Associations Between P-selectin (A)/mg (B) and Adverssupporting
confidence: 69%
“…Increased platelet activity, evidenced by membrane P-selectin expression on circulating platelets, is associated not only with a higher risk of stent thrombosis, but also with a higher risk of later restenosis development (Tschoepe et al, 1993;Murasaki et al, 2007;Osmancik et al, 2008). Plasminogen activator inhibitor-1 (PAI-1), an important member of the plasmin activation system, is a predictor of restenosis after stent placement (Katsaros et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD62P expression is the platelet activation marker most closely associated with increased thrombotic risk. (22,23) P-selectin promotes fibrin deposition, inducing leukocyte accumulation, in areas of vascular injury and arterial thrombosis. (24,25) Furthermore, the binding of P-selectin to PSGL-1 on leukocytes mediates the rolling of leukocytes on adherent and activated platelets.…”
Section: Analysis Of Activated Platelets With Flow Cytometrymentioning
confidence: 99%